Training on Stimulating Moral Values through Storytelling Activities based on Panji Culture - Wati, Epritha Kurnia; Sari, Ayu Titis Rukmana; Putri, Salsabella Aurellya Prastysta; Izdihar, Sausan Ghaida; Rahmawati, Alfina Fadya (CV. Srikandi Kreatif Nusantara in collaboration with Institut Teknologi Mojosari Nganjuk, 2025)
The Panji-based Animated Fairy Tale Video Training for Early Childhood Moral Education aims to improve moral understanding in children through interesting and educational audiovisual media. This program adapts Panji stories, which contain moral values such as loyalty, courage, honesty, and responsibility. Through the use of animated fairy tale videos, it is expected that children can more easily understand and internalize the moral messages conveyed. The study involved data collection through direct observation of children's behavior, questionnaires for teachers and parents, and interviews to measure the impact of the program on children's moral development. The results show that the Panji-based animated fairy tale video is effective in improving children's discipline, empathy, and sense of responsibility. The program also shows the important role of teachers and parents in supporting children's moral education. Nevertheless, challenges such as limited access to technology in some areas and the need for increased training for program managers are still obstacles that need to be overcome. It is hoped that this program can continue to be developed and expanded to provide wider benefits in early childhood character building, as well as preserving local cultural values through traditional stories.